Flow-injection spectrophotometric determination of captopril in pharmaceutical formulations using a new solid-phase reactor containing AgSCN immobilized in a polyurethane resin - Fernando Campanhã Vicentini; Willian Toito Suarez; Éder Tadeu Gomes Cavalheiro; Orlando Fatibello-Filho (Universidade de São Paulo, 2012)
A simple flow-injection analysis procedure was developed for determining captopril in pharmaceutical formulations employing a novel solid-phase reactor containing silver thiocyanate immobilized in a castor oil derivative polyurethane resin. The method was based on silver mercaptide formation between the captopril and Ag(I) in the solid-phase reactor. During such a reaction, the SCN- anion was released and reacted with Fe3+, which generated the FeSCN2+ complex that was continuously monitored at 480 nm. The analytical curve was linear in the captopril concentration range from 3.0 × 10-4 mol L-1 to 1.1 × 10-3 mol L-1 with a detection limit of 8.0 × 10-5 mol L-1. Recoveries between 97.5% and 103% and a relative standard deviation of 2% for a solution containing 6.0 × 10-4 mol L-1 captopril (n = 12) were obtained. The sample throughput was 40 h-1 and the results obtained for captopril in pharmaceutical formulations using this procedure and those obtained using a pharmacopoeia procedure were in agreement at a 95% confidence level. Um procedimento simples de análise por injeção em fluxo foi desenvolvido para a determinação de captopril em formulações farmacêuticas empregando um novo reator em fase sólida contendo tiocianato de prata imobilizado em resina poliuretana obtida a partir de óleo de mamona. O método foi baseado na formação de um mercapto composto de prata, no reator em fase sólida, obtido entre o captopril e Ag (I) imobilizada. Durante a reação, íons SCN- eram liberados e reagiam com Fe3+, gerando o complexo FeSCN2+, que foi continuamente monitorado em 480 nm. A curva analítica foi linear no intervalo de concentração de captopril entre 3,0 × 10-4 a 1,1 × 10-3 mol L-1 com um limite de detecção de 8,0 × 10-5 mol L-1. Recuperações entre 97,5-103% e desvio padrão relativo de 2% para uma solução contendo 6,0 × 10-4 mol L-1 de captopril (n = 12) foram obtidos. A frequência de amostragem foi de 40 h-1 e os resultados obtidos para captopril em formulações farmacêuticas utilizando este procedimento e o da Farmacopeia, estão de acordo em um nível de confiança de 95%.